(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2022)
The process of intellectualization has been characterized as a planned process of accelerating the growth and development of South Africa’s indigenous languages to enhance their effective interface with modern developments, theories and concepts (Finlayson & Madiba, 2002). Corpora are used to develop empirical knowledge about language. A corpus is a collection of naturally occurring texts derived from real life language use in either written or spoken form (cf. Sinclair, 1991). These texts are then processed, stored and accessed by means of computers for use in developing electronic resources of a language. It is thus an important resource in the development of isiZulu Human Language Technologies. Thus, specialized corpora were created for this study and were used as the basis to enquire into the sensitive use of isiZulu with reference to language phenomenon isiHlonipho. Corpus linguistics provides a more objective view of language than introspection, intuition and anecdotes. This study profited from the use of the WordSmith Tools version 6 software program suite, which allowed the researcher to use different programs simultaneously to analyse data.